111k views
1 vote
-18u+16u-7=9 solve for u

2 Answers

4 votes

-18u+16u-7=9

-2u - 7 = 9 (combine like terms)

-2u = 16 (add 7 on both sides)

u = -8

User Peaceful
by
6.0k points
6 votes

Answer:

The correct answer to this problem is u = -8.

Explanation:

To solve this problem, we first must combine like terms on the left side of the equation. This means adding together the two terms that have a "u" multiplied by a number. To combine them, we simply add the coefficients together, as we would with constant values. This is modeled below:

-18u+16u-7=9

-2u - 7 = 9

Next, we want to add 7 to both sides of the equation. This will cancel out the -7 on the left side of the equation, isolating the term with the variable u (what we are trying to solve for).

-2u - 7 + 7 = 9 + 7

-2u = 16

Finally, we want to divide both sides by -2 in order to isolate the variable u. This will get rid of the coefficient of negative 2 and give us our answer.

u = 16/-2 = -8

Therefore, the answer to this question is u = -8.

Hope this helps!

User Sreeram Garlapati
by
5.9k points